Violence in Arab Children’s Literature: Themes, Psychological Insights, and Cultural Reflections - Na’amneh, Mahmoud; Assadi , Jamal; Sindawi, Khaled (Journal of Ecohumanism, 2025)
This study examines the representation of violence in Arab children’s literature, focusing on its depiction of domestic struggles, political conflict, and societal challenges, and its role in fostering emotional resilience and moral development in young readers. Through key texts such as Karma’s Eyes Are No Longer Sad, The Vulture and the Sparrow, and The Monkey and the Thief, the research investigates how these narratives address the realities of Arab-Israeli communities while reflecting cultural values and transmitting moral lessons. The central questions guiding the study are: How does Arab children’s literature portray violence, and does it perpetuate or challenge societal norms around conflict? By exploring these questions, the study evaluates the genre’s strengths—its ability to engage with complex themes and nurture empathy—alongside its limitations, such as an over-reliance on fantasy and insufficient emphasis on long-term conflict resolution. The findings underscore the genre’s dual role as a cultural artifact and a pedagogical tool, with recommendations for creating stories that better balance cultural authenticity with universal moral lessons. This research contributes to the field by offering insights into how Arab children’s literature can empower young readers and foster resilience, cultural pride, and critical thinking in the face of evolving societal challenges.